1998
DOI: 10.1126/science.279.5350.570
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Cerebello-Olivary Projections and Blocking Effect in Classical Conditioning

Abstract: The behavioral phenomenon of blocking indicates that the informational relationship between the conditioned stimulus and the unconditioned stimulus is essential in classical conditioning. The eyeblink conditioning paradigm is used to describe a neural mechanism that mediates blocking. Disrupting inhibition of the inferior olive, a structure that conveys unconditioned stimulus information (airpuff) to the cerebellum prevented blocking in rabbits. Recordings of cerebellar neuronal activity show that the inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(165 citation statements)
references
References 28 publications
10
154
0
1
Order By: Relevance
“…Consistent with this interpretation, it has been shown that reversible inactivation of the NI-DAO inhibitory pathway disrupts the blocking effect in eyelid conditioning (Kim, Krupa, & Thompson, 1998).…”
Section: Extinction and Blocking Are Also Mediated By The Inhibitory supporting
confidence: 61%
“…Consistent with this interpretation, it has been shown that reversible inactivation of the NI-DAO inhibitory pathway disrupts the blocking effect in eyelid conditioning (Kim, Krupa, & Thompson, 1998).…”
Section: Extinction and Blocking Are Also Mediated By The Inhibitory supporting
confidence: 61%
“…7). Neurons carrying prediction errors are also found in brain structures other than the dopamine system 7 , particularly in the climbing 庐bre projection to cerebellar Purkinje cells 11,12,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier review, 204 we included a section entitled 'how is nonreinforcement detected,' which noted that the detection of the nonoccurrence of an expected US is a critical feature of extinction training protocols and, as such, an understanding of the mechanisms by which this occurs will be critical to a full understanding of extinction. At that time there was very little information on the so-called 'error signal' involved in Pavlovian fear conditioning, although work in other paradigms including eyeblink conditioning in rabbits 205 and appetitive learning in nonhuman primates 206 held promise that such a signal could be identified and experimentally manipulated. Since then some exciting work by Gavan McNally and co-workers has argued convincingly that a fear error signal exists and involves endogenous opioid signaling within the ventrolateral periaqueductal gray (vlPAG).…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%